Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1177/154230501406800104
|View full text |Cite
|
Sign up to set email alerts
|

In the Shadow of Death: Existential and Spiritual Concerns among Persons Receiving Palliative Care

Abstract: This study explores existential and spiritual concerns from the perspective of people receiving palliative care. It examines the meaning of these concerns, their influence on people's lives and investigates the connections between them. In-depth qualitative interviews were conducted with ten persons. Findings reveal existential and spiritual aspects as interconnected and an integral part of the participants' everyday existence. It concludes with a call for a better understanding of these phenomena in the palli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…This study formed part of a larger study on spirituality among persons receiving palliative care in Iceland, which used a mixed methods approach (Asgeirsdottir et al . , ). The qualitative part of this larger study revealed six main spiritual themes in which faith and spiritual practices especially prayer, were important elements of how persons perceived their spirituality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study formed part of a larger study on spirituality among persons receiving palliative care in Iceland, which used a mixed methods approach (Asgeirsdottir et al . , ). The qualitative part of this larger study revealed six main spiritual themes in which faith and spiritual practices especially prayer, were important elements of how persons perceived their spirituality.…”
Section: Discussionmentioning
confidence: 99%
“…The results from the SWB measure also represent issues that were found important in the qualitative part of the larger study on spirituality in Iceland and thereby gives the SWB measure face validity (Asgeirsdottir et al . , ). Furthermore, the findings indicate that the EORTC QLQ‐SWB can be used to assess SWB among persons receiving palliative care for cancer and possibly also as an intervention tool for addressing the complex realm of spiritual concerns and needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The search identified, among the 67 studies in this review that, 77,6% of them see the life quality categories a driving force for the palliative treatment followed by the spirituality category at 70,14%. The spiritual intervention resulted in a significant increase of hope, happiness and life satisfaction (P <0,05) [17]. The spirituality is one of the main aspects of palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…The spiritual intervention resulted in a significant increase of hope, happiness and life satisfaction (P <0,05) [17]. The spirituality is one of the main aspects of palliative care.…”
mentioning
confidence: 99%